2016
DOI: 10.1016/j.jval.2016.03.1575
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Treatment Costs of Follicular Lymphoma: A Population-Based Discrete Event Simulation

Abstract: A147patient population. Based on a representative population-based patient-cohort, the objective of this study was to develop a decision model that could reflect realworld practice and predict the costs throughout treatment pathway. Methods: All patients newly diagnosed with FL in the UK's population-based Haematological Malignancy Research Network (www.hmrn.org) between 2004 and 2011 were followed until 2014 (n= 741). The mapped treatment pathways, alongside cost information derived from the National Tariff 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Three studies and two abstracts in FL met the eligibility criteria for final inclusion. One study assessed patients who received prior treatment [30], while the other four included only treatment-naïve patients [26,[31][32][33]. Treatment regimens, when reported, all incorporated the use of R in monotherapy or combination.…”
Section: Costs/resource Usementioning
confidence: 99%
See 3 more Smart Citations
“…Three studies and two abstracts in FL met the eligibility criteria for final inclusion. One study assessed patients who received prior treatment [30], while the other four included only treatment-naïve patients [26,[31][32][33]. Treatment regimens, when reported, all incorporated the use of R in monotherapy or combination.…”
Section: Costs/resource Usementioning
confidence: 99%
“…Treatment regimens, when reported, all incorporated the use of R in monotherapy or combination. The time horizon ranged from 1 year [30] to a lifetime [32,33]. Studies were conducted from the health care payer perspective, when reported [30][31][32]34].…”
Section: Costs/resource Usementioning
confidence: 99%
See 2 more Smart Citations